A Daily, Respiratory Therapist Assessment of Readiness to Liberate From Venovenous Extracorporeal Membrane Oxygenation in Patients With Acute Respiratory Distress Syndrome. (3rd December 2021) - Pratt, Elias H.; Mausert, Sarah; Wilson, Michael D.; Emerson, Logan J.; Navuluri, Neelima; Pulsipher, Aaron M.; Brucker, Amanda; Green, Cynthia L.; Bonadonna, Desiree K.; Bryner, Benjamin S.; Rackley, Craig R.
Abstract : Objectives: We assessed the effect of implementing a protocol-directed strategy to determine when patients can be liberated from venovenous extracorporeal membrane oxygenation on extracorporeal membrane oxygenation duration, time to initiation of first sweep-off trial, duration of mechanical ventilation, ICU length of stay, hospital length of stay, and survival to hospital discharge. Design: Single-center retrospective before and after study. Setting: The medical ICU at an academic medical center. Patients: One-hundred eighty patients with acute respiratory distress syndrome managed with venovenous extracorporeal membrane oxygenation at a single institution from 2013 to 2019. Interventions: In 2016, our institution implemented a daily assessment of readiness for a trial off extracorporeal membrane oxygenation sweep gas ("sweep-off trial"). When patients met prespecified criteria, the respiratory therapist performed a sweep-off trial to determine readiness for discontinuation of venovenous extracorporeal membrane oxygenation. Measurements and Main Results: Sixty-seven patients were treated before implementation of the sweep-off trial protocol, and 113 patients were treated after implementation. Patients managed using the sweep-off trial protocol had a significantly shorter extracorporeal membrane oxygenation duration (5.5 d [3–11 d] vs 11 d [7–15.5 d]; p < 0.001), time to first sweep-off trial (2.5 d [1–5 d] vs 7.0 d [5–11 d]; p < 0.001), duration of mechanical ventilation (15.0 d [9–31 d] vs 25 d [21–33 d]; p = 0.017), and ICU length of stay (18 d [10–33 d] vs 27.0 d [21–36 d]; p = 0.008). There were no observed differences in hospital length of stay or survival to hospital discharge. Conclusions: In patients with acute respiratory distress syndrome managed with venovenous extracorporeal membrane oxygenation at our institution, implementation of a daily, respiratory therapist assessment of readiness for a sweep-off trial was associated with a shorter time to first sweep-off trial and shorter duration of extracorporeal membrane oxygenation. Among survivors, the postassessment group had a reduced duration of mechanical ventilation and ICU lengths of stay. There were no observed differences in hospital length of stay or inhospital mortality.